How “mood‐incongruent psychosis” was included under affective disorders in the DSM‐III - Hiroyuki Takiue (PCN Reports, 2025)
Abstract The Diagnostic and Statistical Manual, Third Edition (DSM‐III), the prototype of the modern DSMs, differed from previous traditions in American psychiatry in that it was etiologically agnostic. It also represented a re‐importation of German psychiatry for the first time since Freud. An exception, however, was the hierarchical relationship between mood and psychosis, which was weighted in favor of mood in the United States. Specifically, mood‐incongruent psychosis was considered a symptom that could also occur in affective (mood) disorders. This was a decision that also differed from the Ninth Revision of the International Statistical Classification of Disease, which was published 3 years before the DSM‐III. It was not until the nineteenth century that a distinction was made between mood and psychosis. In Germany, the emphasis was on psychosis, whereas in the United States, under the strong influence of Adolf Meyer, the emphasis was on depression. Hallucinatory and delusional states, later summarized as Kurt Schneider's “first‐rank symptoms” (FRS), were also incorporated into the framework for mood disorders. Subsequently, the United States entered the heyday of psychoanalysis, while German descriptive psychopathology was difficult to accept. When the DSM‐III was drafted in the 1970s, the FRS were “cut out” from that descriptive psychopathology and introduced. However, since that time, the FRS, along with other mood‐incongruent psychoses, have lost their specificity for schizophrenia and organic psychosis.